Análisis de la influencia de las relaciones interpersonales para el crecimiento de la Cooperativa de Ahorro y Crédito integración solidaria ltda. del cantón Salcedo - Coque Coque, Silvia Mariela (2015)
The research aimed to analyze the influence of interpersonal relationships for growth of the "Cooperativa de Ahorro y Crédito Integración Solidaria Ltda." of Salcedo Canton, for implementing a strategic plan consists of actions that help to the institution in order to improve their activities through good decisions. This project was based on methods: inductive - deductive, analysis - synthesis of information from books and websites also relied on techniques such as survey, interview and observation, similarly, the SWOT….